Síntese e caracterização de óxidos de zinco e de magnésio suportados em A1SBA-15 para produção de biodiesel - Galvão, Luzia Patrícia Fernandes de Carvalho (2012)
To overcome the challenge of meeting growing energy demand in a sustainable way, biodiesel has shown very promising as alternative energy can replace fossil fuels, even partially. Industrially, the biodiesel is produced by homogeneous transesterification reaction of vegetable oils in the presence of basic species used as catalysts. However, this process is the need for purification of the esters obtained and the removal of glycerin formed after the reaction. This context, the alternative catalysts have that can improve the process of biodiesel production, aiming to reduce costs and facilitate its production. In this study, the AlSBA-15 support with Si / Al ratio = 50 was synthesized, as like as the heterogeneous catalysts of zinc oxide and magnesium supported on mesoporous AlSBA-15 silica, in the concentrations of 5, 10, 15 and 30 %, relative to the support. The textural properties and structural characterization of catalysts and supports were determined by techniques: X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) coupled to the chemical analyzer, adsorption / desorption of N2, thermal analysis (TG / DTG), absorption spectroscopy in the infrared (FTIR) and X-ray photoelectron spectroscopy (XPS). Characterization results indicated that the support AlSBA-15 retained the hexagonal ordered after the incorporation of zinc oxide and magnesium oxide in the holder. For heterogeneous catalysts, ZnO-AlSBA-15, that was observed the presence of zinc oxide nanoparticles dispersed in the surface and interior channels of the mesoporous and microporous support. The catalytic activity was evaluated by the transesterification reaction of sunflower oil via methylic route, and some reaction parameters were optimized with the most active catalyst in biodiesel production by sunflower oil. For the series of heterogeneous catalysts, the sample with 30 % ZnO supported on AlSBA-15 showed a better conversion of triglyceride to methyl esters, about 95.41 % of reaction conditions: temperature 175 °C, with molar ratio of 42:1, stirring at 200 rpm and under a pressure of 14 bar for 6 h. The catalyst MgO-AlSBA-15 showed no catalytic activity in the studied reactions